(3GdaJM GdbQjH aj SjQI GdMHjH (B[ (3fXe SjQI GHf gTGe (B]s - (3GHf GdTgjO , eMeO Hf EHQGgje, CHh GdaJM , aJM GdOjf,J (B793 (3g` s
(3ChdgG (B:s
(3PcQ eG cGf HYO ZRhI HOQ ai HbjI GdYGe GdKGfi ef GdgLQI PcQ CehQ HYO eQLY GdQShd ef HOQ ai PG GdYGe JCJi ai aUhd s
(3BNQgG (B:s
(3ef cJGHg Udi Gddg Ydjg hSde Edi cSQi edc GdaQS eY YHO Gddg GHf MPGaI MJi GbJSefG cfRg HGdCSge afGdfG ai GdbSe Cda OQge ced GdLRA GdKGfi ef GdaJM GdbQjH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs